KINERJA DINAS PERINDUSTRIAN, MIGRASI DAN TENAGA KERJA KABUPATEN MERAUKE DALAM PELAKSANAAN KEBIJAKAN TENAGA KERJA - Ransta Lekatompessy (Universitas Musamus, Merauke, Papua, 2016)
The analysis on the performance of the Government’s program is still very important until now because it’s value. The measurement on the Performance of a program can be viewed as an evaluation to value the success or failure of program implementation. However, it is hard to do, since performance measurement system program has not been applied. The objective of this study is to analyze the performance and it’s determinants of the Department of Industry, Migration and Man Power in implementing the Labor Policy. In accordance with its focus, this research used descriptive method to answer the research questions. Observation technique, interview, and documentation technique are the main methods in data collection. The primary and secondary data is used in this study.The research findings indicate that the performance of the Department of Industry, Migration and Man Power in implementing the Labor Policy at Merauke Regency has not optimally achieved. It can be seen from the indicators of responsiveness, responsibility and accountability. This study also proves that the factors such as the characteristic of the policy, institutional and environmental characteristics are very influential to the performance of the Labor Policy at Merauke Regency. One important factor among these factors is institutional factor mainly the number and quality of instructors and coaching staffs. The improvement on the quality and quantity of instructors and coaching staffs can be done by technical guidance and competency test in accordance with their expertise.